Novel classification of Achilles tendon ruptures - Yu. D. Kim; Yu. I. Bardovskaya; S. N. Romanova; A. S. Pankratov; D. S. Shitikov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
In the literature, the treatment of patients with Achilles tendon ruptures begins with diagnosis and diagnosis. Depending on the classification of Achilles tendon rupture, treatment tactics are determined. From our point of view, the existing classification of Achilles tendon ruptures does not sufficiently reflect and systematize the approach to surgical treatment, which served as a more detailed study and addition to the existing classification of Achilles tendon ruptures.